Systematic Literature Review: Research on Improving Student Learning Outcomes Through Google Meet Using Vosviewer, 2019-2022 - Mohammad Nawa Aba-‘Ilmi (Majalah Bisnis & IPTEK, 2023)
This research aims to examine the development of research that addresses improve student learning outcomes through google meet. This research was conducted to determine: (1) a map of the development of the number of publications researching improve student learning outcomes through google meet; (2) know which scientific articles have the highest number of citations; (3) know the development map of scientific publications based on keywords. The data source used in this study is scientific articles in the google scholar database with google meet keywords, with article title categories, abstracts, and keywords in the range 2019-2022. The search results show that 318 scientific articles match keywords based on Harzing's Publish or Perish app. The results showed that research on improve student learning outcomes through google meet in 2019 - 2022 which was the highest in the google scholar database occurred in 2021 and reached 141 publications or 44%. Meanwhile, the publication that has the highest number of citations is (A Darmuki, 2020) which is quoted 154 times. A map of the development of scientific publications based on google meet’ keywords analyzed using the VOSViewer application shows that the research map is divided into 5 clusters.